Показники роботи протитискової турбіни ПР-6-35/5/1,2 в системах теплофікації - Чепурний, М. М.; Ткаченко, С. Й.; Резидент, Н. В. (НТУ "ХПІ", 2014)
Здійснено аналіз і визначено основні показники ефективності роботи турбогенератора з паровою турбіною ПР-6-35/5/1,2 при різних парових і електричних навантаженнях. Визначено питому витрату умовного палива на сумісне виробництво теплової і електричної енергії, коефіцієнт використання теплоти палива та частку теплоти палива, яка витрачена на виробництво теплової енергії. З використанням вище вказаних показників встановлено, що найбільш ефективна робота зазначеної турбоустановки досягається за умови номінальної електричної потужності та допустимої витрати пари через відсік низького тиску, а зменшення тиску в регульованому відборі турбіни зумовлює підвищення ефективності її роботи. Крім того, показано, що недовантаження протитискової турбіни з відбором пари для будь-яких режимів роботи призводить до суттєвого погіршення ефективності роботи паротурбінної установки.

The main indices of the operation efficiency of the turbine generator with the steam turbine PR-6-35/5/1,2 for different steam and power loadings have been determined and analyzed. The specific consumption of the reference fuel for joint production of thermal and electric energy, the fuel heat utilization coefficient and the fuel heat fraction spent for the thermal energy production have been determined. The use of the indices given above allowed us to establish that the most efficient operation of the given turbine unit is reached under the condition of nominal electric power and permissible steam flow rate through the low pressure compartment and a decrease in pressure of the regulated steam bleeding of the turbine will condition an increase in the efficiency of its. operation. In addition it has been shown that the underload of the back-pressure turbine with the steam bleeding in any operation modes results in the considerable degradation of the operation efficiency of steam-turbine unit.

specific flow rate
Operation indices of the back-pressure turbine PR-6-35/5/1,2 in cogeneration systems
Keywords: парогенератор; парова турбіна; електрогенератор; умовне паливо; питома витрата; steam generator; steam turbine; power generator; conventional fuel